Dental Professionals' Engagement in Tobacco, Electronic Cigarette, and Cannabis Patient Counseling. (April 2020) - Chaffee, B.W.; Urata, J.; Couch, E.T.; Silverstein, S.
Objectives: California features low smoking prevalence, cautionary electronic cigarette (e-cigarette) public messaging, and legal recreational cannabis: a unique landscape for dental professionals to navigate tobacco cessation promotion. This cross-sectional study assessed California dental professionals' self-reported tobacco patient counseling behaviors and the correlates of providing such assistance. Methods: Statewide surveys of dental hygienists (n = 701) and dentists (n = 725) were distributed electronically. The dentist survey was weighted for sampling and nonresponse. Prevalence of asking patients about use was compared for cigarette and noncigarette products (e.g., e-cigarettes, cannabis). Multivariable models identified independent correlates of providing cessation assistance to tobacco-using patients. Results: Respondents reported frequently (often/always) documenting patient tobacco use (hygienists: 80%; dentists: 73%) but less commonly provided forms of assistance (hygienists: 27%–49%; dentists: 10%–31%). Most respondents asked patients about cigarette smoking, but noncigarette product use (cigar, hookah, pipe, e-cigarette, or cannabis) was not commonly assessed. Greater confidence and willingness to assist were positively associated with providing assistance in multivariable models, but perceived barriers (e.g., lack of time and remuneration) were not. Results were robust to model specifications. Conclusions: California dental professionals often ask about smoking but lag in providing cessation assistance and inquiring about noncigarette products. Successful efforts to encourage dental professionals' engagement in tobacco prevention and cessation must enhance providers' self-efficacy and motivation and likely will require system and organizational change. Knowledge Transfer Statement: Study findings identify substantial gaps in dental professionals' engagement in patient tobacco cessation. The results identify correlates of providing assistance and of dental professionals' willingness and confidence to do so, which could serve to inform interventions to support and enhance engagement.